The key elements that influencing economic growth in Malaysia / Natasha Zuliana Zulfakar - Zulfakar, Natasha Zuliana (Faculty of Business and Management, 2018)
The purpose of this study is to examine the key elements that influencing economic growth in Malaysia via time series data. This study employs the ordinary least square (OLS) method and the macroeconomic variables used consist of inflation rate, exchange rate, foreign direct investment, tourism receipts and trade openness as independent variables taken in the period from quarter one 1970 to 2016. The results show that the foreign direct investment, tourism receipts and trade openness shows a significant positive relationship while the exchange rate shows significant negative relationship. However, inflation rate is found to have insignificant negative effects towards economic growth in Malaysia.